The role of independent audit in post customs control - Петрик, Олена Анатоліївна; Мариніч, Ілля Олександрович (Technology audit and production reserves, 2015)
Developing of post customs control is in the highlight of customs authorities, national and foreign scientists. In that time there is no unified understanding of “post customs control” and “post customs audit” terms, like as theirs normative definition. Necessity of creation new Custom Service in Ukraine, modeled after the European Union, caused by economic integration process. In that time it’s a reason of conversion to international standards of custom control, especially Kyoto Convention. In this context strengthening of controlling and auditing function as modern form of customs control becomes still more actual. Place and role of independent audit in post customs control system is determined by analysis of modern determination of terms “post customs control” and “post customs audit”, legal requirements for customs procedures and foreign economic activity audit. In spite of vast resources of auditing firms their capacity is hardly used for post customs control. First of all it is determined be imperfection of national legislative base and absence of customs authorities special efforts and Auditor’s Chamber of Ukraine. For acceleration of post customs control implementation in Ukraine it is necessary to amend legislative and normative acts for clear determination of post audit functions. It is also recommended to work out essential methodic basis.